Characterization of volatile organic compounds at a roadside environment in Hong Kong: An investigation of influences after air pollution control strategies. (December 2015) - Huang, Yu; Ling, Zhen Hao; Lee, Shun Cheng; Ho, Steven Sai Hang; Cao, Jun Ji; Blake, Donald R.; Cheng, Yan; Lai, Sen Chao; Ho, Kin Fai; Gao, Yuan; Cui, Long; Louie, Peter K.K.
Abstract: Vehicular emission is one of the important anthropogenic pollution sources for volatile organic compounds (VOCs). Four characterization campaigns were conducted at a representative urban roadside environment in Hong Kong between May 2011 and February 2012. Carbon monoxide (CO) and VOCs including methane (CH4 ), non-methane hydrocarbons (NMHCs), halocarbons, and alkyl nitrates were quantified. Both mixing ratios and compositions of the target VOCs show ignorable seasonal variations. Except CO, liquefied petroleum gas (LPG) tracers of propane, i -butane and n -butane are the three most abundant VOCs, which increased significantly as compared with the data measured at the same location in 2003. Meanwhile, the mixing ratios of diesel- and gasoline tracers such as ethyne, alkenes, aromatics, halogenated, and nitrated hydrocarbons decreased by at least of 37%. The application of advanced multivariate receptor modeling technique of positive matrix factorization (PMF) evidenced that the LPG fuel consumption is the largest pollution source, accounting for 60 ± 5% of the total quantified VOCs at the roadside location. The sum of ozone formation potential (OFP) for the target VOCs was 300.9 μg-O 3  m −3, which was 47% lower than the value of 567.3 μg-O 3  m −3 measured in 2003. The utilization of LPG as fuel in public transport (i.e., taxis and mini-buses) contributed 51% of the sum of OFP, significantly higher than the contributions from gasoline- (16%) and diesel-fueled (12%) engine emissions. Our results demonstrated the effectiveness of the switch from diesel to LPG-fueled engine for taxis and mini-buses implemented by the Hong Kong Special Administrative Region (HKSAR) Government between the recent ten years, in additional to the execution of substitution to LPG-fueled engine and restrictions of the vehicular emissions in compliance with the updated European emission standards. Highlights: A series of control strategies has been implemented by HKSAR in recent years. Characteristics of VOCs were compared at roadside between 2003 and 2011/2012. Besides alkanes, the mixing ratios of other VOCs decreased by >50% since 2003. LPG fuel consumption becomes the largest contributor to the pollution. The sum of OFP for the target VOCs was reduced by 47% compared to that in 2003.